2001
DOI: 10.1055/s-2001-10707
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study comparing human albumin vs. reinfusion of ultrafiltrate-ascitic fluid after total paracentesis in cirrhotic patients with tense ascites

Abstract: Although, total paracentesis associated with human albumin substitution has shown to be a rapid, effective and safe treatment of diuretic refractory ascites in advanced liver cirrhosis, it implies high costs and has a limited availability. Therefore an alternative procedure the reinfusion of concentrated ascites has gained popularity in recent years (Smart et al. 1990; Grazioto et al. 1997). It was the aim of the study to compare human albumin substitution vs. reinfusion of ascitic-ultrafiltrate after total pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 11 publications
1
21
1
Order By: Relevance
“…In our study, statistically significant decreased blood pressure was observed and confirmed in almost all cases after paracentesis, but we consider that such a decrease had no clinical significance as it did in Stephenson's report. Regarding body temperature, reinfusion of unfiltered and concentrated ascites reportedly caused fever higher than 38°C in 42.8% of patients, even though no bacterial contamination was found in reinfused ascites fluid . In this study, the observed changes were less than or equal to grade 1 in the scale of CTCAE ver.…”
Section: Discussionmentioning
confidence: 46%
“…In our study, statistically significant decreased blood pressure was observed and confirmed in almost all cases after paracentesis, but we consider that such a decrease had no clinical significance as it did in Stephenson's report. Regarding body temperature, reinfusion of unfiltered and concentrated ascites reportedly caused fever higher than 38°C in 42.8% of patients, even though no bacterial contamination was found in reinfused ascites fluid . In this study, the observed changes were less than or equal to grade 1 in the scale of CTCAE ver.…”
Section: Discussionmentioning
confidence: 46%
“…Generally, fever is a clinically significant problem in CART [23], and the Kansai CART Study Group indicated that the processing speed was related to body temperature elevation [4]. Other possible factors involved are cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Borzio et al reported that 12% of their patients who received concentrated ascites developed fever and chills, even after infection in the ascites had been ruled out (5). Zaak et al reported that pyrexia and chills were observed in 43% of the patients, although the ultrafiltrate was found to be uninfected (6). In conventional CART, inflammatory substances such as interleukins are produced by white blood cells; when these cells are returned intravenously, they can cause high fevers because they are further concentrated via the concentrating membrane.…”
Section: Discussionmentioning
confidence: 99%